â€œGregetâ€ in The Surabaya Ngrema Dance Performance Representation of The Value of The Fighting Spirit of Arek Surabaya - Wahyudiyanto (Institut Seni Indonesia Denpasar, 2023)
In the Ngrema Surabayan dance performance there is an expression called Greget. Greget that the audience felt are in form of vibrations when the dancers make movements. Suspected Greget is a dancer's interpretation work to present certain figures as a reflection of dance themes. This research uses a descriptive approach by applying technical and kinesthetic analysis of motion. Ethnographic methods are used as data collectors and compile narratives to realize an understanding of Greget. The results of the study explained that the Greget in Surabayan Ngrema Dance was formed by the quality of technique and kinesthetic. The technique as the application of the basic guidelines for the implementation of the motion presents kinesthetic that is a sense of gallant, agile, and authoritative. Sense of movement is the implication of a deep appreciation of the value of heroism. The value of heroism as a dance theme is represented by dancers from the Cakraningrat figure the regent of Madura. An imaginary expression of the spirit of struggle in the Ngrema Surabayan dance embodies the legitimacy of the Surabaya City hero identity.